A methodological approach to acquire high-quality spectra on milk protein concentrate using a Near Infrared (NIR) transflectance probe. Issue 3 (June 2021) - Pu, Yuanyuan; Marín, Dolores Pérez; O'Shea, Norah; Garrido-Varo, Ana
This article introduces the project NIR4Dairy and presents the studies currently undertaken. Based on an industry partner's interest, one of the research objectives is to quantify the lactose content of milk protein concentrate in a very low lactose concentration range (e.g. 0.07–0.3%), using a Near Infrared (NIR) transflectance probe connected to a Fourier Transform-Near Infrared (FT-NIR) instrument. An approach to acquire high-quality and repeatable spectra of milk protein concentrate is reported.